Essays on consumer welfare and new food product development in West Africa - Nakelse, Tebila (Kansas State University, 2019)
Economic indicators (price, income, taste, and preference) and non-economic (information, time and equipment, food quality and safety) indicators are key elements of the food environment that need further investigation in developing countries. The main objective of this thesis is to evaluate the effect of these factors on consumer behavior in West Africa, especially in Niger and Burkina Faso. The first essay analyzes the implications of world cereal price shocks on rural household welfare in Burkina Faso by establishing a link between farmers and world markets. The approach is grounded in agricultural household modelling with the world price for cereals, transmitted to farmers, through local producer and consumer prices. Household net welfare after a price shock is derived as a function of behavioral responses to local price change induced by the international price shock. The main result of this analysis is that the increase in prices during the period from 2006 to 2014 is translated to welfare improvement ranging from 0.02 percent for 2006 to 0.06 percent for 2011 for farmers in Burkina Faso. The second essay assesses urban consumers' preference for food quality attributes of value-added cereal products in Niamey, Niger. It combines qualitative and quantitative methods to evaluate the effect of quality attributes on consumers' food choice. A particular focus is placed on assessing consumers' marginal willingness-to-pay (WTP) for quality attributes in an experimental setting. The evaluation accounted for taste and preference heterogeneity inherent to consumers’ responses to changes in quality attributes. The results suggest market demand inferred from significant marginal WTP for the nutritional quality attribute as measured by the expiration date, the presence of micronutrients, and the country of origin of the product. In addition, demand is found to be highly heterogeneous across consumers socio-demographic and economic characteristics. As a result, better communication and appropriate targeting by food processors and policymakers could be an additional tool to enhance food quality and diet through the market. Finally, the third essay theoretically and empirically assesses the impact of a time-saving food attribute on consumer’s food choice in urban areas of Niger. The theoretical assessment relied on a ``Beckerian’’ time allocation model to derive how a time-saving food product affects consumers' utility and food choice. The empirical approach combines hedonic tasting, random utility and a latent class framework to identify taste heterogeneity patterns underlying consumers' choice. Both the hedonic and latent class models confirm the theoretical prediction that a time-saving characteristic can either increase or decrease the demand for food that embodies the attributes. A significant market segment of about 38% includes consumers with a positive valuation of the time-saving product, highlighting the potential of this attribute to increase consumers welfare, reduce energy use and prevent food preparation-related health issues.
Keywords: Price Analysis; Consumer Welfare; Time allocation; West Africa